Innovative Research Methods to Advance Precision in Home Visiting for More Efficient and Effective Programs. (9th July 2019) - Supplee, Lauren H.; Duggan, Anne
Abstract: Home visiting during early childhood can improve a range of outcomes for children and families. As evidence‐based models are implemented across the nation, two questions have emerged. First, can home visiting improve outcomes more efficiently? Second, can overall effects be strengthened for specific subgroups of families? For the past several decades, research focused on testing the average effects of home visiting models on short‐ to long‐term outcomes has found small impacts. These effects are not the same for all families. The field needs new evidence produced in new ways to overcome these challenges. In this article, we provide an overview of the evidence in this field, including what works and for whom. Next, we explain precision approaches to various fields and how this approach could be used in home visiting programs. Research on precision home visiting focuses on the ingredients of home visiting models, collaborating with practitioners to identify the ingredients and testing them on near‐term outcomes, and using innovative study designs to learn more quickly what works best for which families. We conclude by proposing four pillars of research that will help achieve precision home visiting services.